(untitled) (Ushuluddin International Conference (USICON), 2019)
This study aims to reveal the role of religion in the formation of civil society with a functional sociology approach. At present, the Indonesian people are grieving over the earthquake that hit Yogyakarta, Klaten and surrounding areas. This was compounded by the existence of hot mud in Sidoarjo, the events of tsunami in Aceh, Palu and its surroundings which all had a lot of harm to the people. This condition does not rule out the possibility of various forms of violence, such as: riots, deprivation, looting, conflict and so on. Various kinds of violence are not only motivated by social aspects but also other aspects such as: economic, political, ethnic, and including religion. From this study, the religions in Indonesia with the concepts of harmony and tolerance derived from the scriptures or their respective traditions, such as Islam, Catholicism, Protestantism, Hinduism, Buddhism, Confucianism and the civil religion or indigenous religion, both normatively and historically, they are involved in solving national problems through their respective ways such as through interfaith dialogue and in other ways, such as in solving problems of poverty, backwardness, colonialism and so on. With integrative functions as unifying and disintegrating as a deviant policy of power or government, it turns out that the religions, including the civil religion, play a role in realizing the existence of civil society, which is a polite and tolerant society towards one another, who regulates itself through various institutions, without government interference, and which are free from coercion, threats and military violence. Whatever organization or institution or NGO (NGO) they conduct, the followers of religion as part of the Indonesian Republican citizens can participate in realizing a society that is inclusivism, humanism / egalitarianism, tolerance and democracy; the people who are calm tentrem kerto raharjo; or a just, prosperous and prosperous society.